Development of prostate cancer in a patient with primary hypogonadism: intratumoural steroidogenesis in prostate cancer tissues. (23rd October 2012) - Arai, S.; Shibata, Y.; Nakamura, Y.; Kashiwagi, B.; Uei, T.; Tomaru, Y.; Miyashiro, Y.; Honma, S.; Hashimoto, K.; Sekine, Y.; Ito, K.; Sasano, H.; et al.
Summary: Intratumoural steroidogenesis may play a significant role in the progression of prostate cancer (PC) in the context of long‐term ablation of circulating testosterone (T). To clarify the mechanism accounting for the progression of PC in a 74‐year‐old man who had undergone bilateral orchiectomy when he was 5 years old, we performed immunohistochemical studies of androgen receptor (AR) and steroidogenic enzymes in the prostate. We also measured steroid hormone levels in the serum and prostate, as well as mRNA levels of genes mediating androgen metabolism in the prostate. Positive nuclear staining of AR was detected in malignant epithelial cells. The levels of androstenedione (Adione), T, and 5‐alpha dihydrotestosterone (DHT) in the serum of the patient were similar to those in PC patients receiving neoadjuvant androgen deprivation therapy (ADT), but were higher in the patient's prostate than in PC patients not receiving ADT. The gene expression of CYP17A1 and HSD3B1 was not detected, whereas that of STS, HSD3B2, AKR1C3, SRD5A1, and SRD5A2 was detected. Moreover, cytoplasmic staining of HSD3B2, AKR1C3, SRD5A1, and SRD5A2 was detected in malignant epithelial cells. Hence, in the present case (a man with primary hypogonadism), steroidogenesis in PC tissues from adrenal androgens, especially dehydroepiandrosterone sulphate, was the mechanism accounting for progression of PC. This mechanism might help elucidate the development of castration‐resistant PC.